Analisis Pelatihan dan Pengembangan Karyawan Terhadap Ekspansi Bisnis Es Teh Jumbo - Vesti Nadari Artisti; Apprilisda Ranica Putri (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Human resources (HR) to support the sustainability and growth of the business. This study examines the implementation of training and development programs at UMKM Es Teh Jumbo Kay in Madiun as part of a strategy to improve employee performance in the face of business expansion. Training focuses on improving technical skills, such as machine operation and customer service, while development is directed towards preparing employees to occupy managerial positions in the new branch. The research uses a descriptive qualitative approach to understand the dynamics of the implemented program. The findings indicate that training and development programs make a significant contribution to improving employee performance and support business readiness in expanding their business networks. Thus, human resource management through training and development has proven to be an important factor in supporting the competitiveness and sustainability of SMEs.